REPRODUKSI SAPI PERAH FRIESIAN HOLSTEIN PADA BERBAGAI PERIODE LAKTASI - Ali Mahmud; Woro Busono; Puguh Surjowardojo (JURNAL ILMIAH PETERNAKAN TERPADU, 2018)
The purpose of this research is to compare the efficiency of reproductive performance Friesian Holstein (FH) in various lactation periods. The material used in this research is obtained from the records of reproductive performance Friesian Holstein (FH) cattle from Australia and has been developed in PT. Greenfield Indonesia farm. Datas were using 473 heads dairy cattle these were 100 heads for each lactation period I up to IV and 73 heads for lactation period V. The variable measured were efficiency of reproductive include service per conception (S/C); days open (DO) and calving interval (CI). The datas were analyzed using Completely Randomize Design one-way analyzes of variance (one way lay out) and if the result showed differences, the research will be continued using Least Significant Difference (LSD). The results showed that the higher lactation period of dairy cattle the greater the S/C, DO and CI (P<0.01). In lactation period I and II earned S/C value 2.6±1.3 and 2.1±1.1 were lower than lactation period III, IV and V which earned value 3.7±2.0; 4.2±2.1 and 4.1±2.3. DO in lactation I and II as118.3±49.7 days and 97.6±35.1 days were lower than lactation period III, IV, and V is 153.5±65.8 days;  168.2±81.5 days and 59.2±74.7 days. The lower CI was in period lactation II 365.8±36.9 days compared with lactation period III, IV  and V as 393.8±54.5 days; 406.1±78.3 days and 401.3±65.1 days. Conclusion of this research was lactation period has an effect on the performance of FH dairy reproduction, the higher of lactation period would increase S/C, DO and CI. Keywords : Calving Interval, Days Open, Friesian Holstein Cattle, Lactation Period, Service Per Conception.